H. C. Andersen’s fairy tales as a possible source for the genesis of “A Dream Play” by A. Strindberg - Ruskova, Elizaria (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2024)
The article compares Strindberg’s “A Dream Play” with two tales by H. C. Andersen – “The Galoshes of Fortune” and “The Nightcap of the Pebersvend” – focusing on the concepts of space-time and the function of the stage or narrative object. Central to the analysis is the category of the “uncanny”, defined by Tsvetan Todorov as “experience of the borders”. The emphasis on spatial motifs and their dynamics creates the effect of “the uncanny”, which becomes an aesthetic category connecting Andersen’s Romanticism with Strindberg’s Modernism.
Keywords: the “uncanny”; Andersen; Strindberg; the functions of a narrative/stage object